A study to assess the effectiveness of planned teaching on knowledge regarding minor ailments during antenatal period among primi gravida mothers in selected hospitals of Sangli city, Maharashtra, India - Rohit Dhanawade, Archana (International Journal of Nursing Research, 2023)
Pregnancy is creative and productive period in the life of a woman. There are some common problems that a woman might experience during pregnancy and because they are not threatening their life, they are called minor. There is high incidence of minor ill health in the population. Aim: To assess the existing knowledge regarding minor ailments during antenatal period, To evaluate the effectiveness of planned health teaching regarding minor ailments during antenatal period, To compare the result with selected demographical variables. Methods: The research design was quasi experimental. The data was collected with the structured questionnaire; samples were 60 antenatal mothers attending ANC OPD. Result: pre-test mean was 1.74 and post-test 2.13. This differences was statistically significant as p value o.ooo level with„t‟ value of -9.527. In educational status 25 women‟s have acquired primary education, 24 of the women have acquired secondary knowledge, and 10 of the women have acquired graduate degree and only 1 woman. In the area vise distribution most (42) of the women belong from the urban areas while (18) of the women are from rural areas. Conclusion: Planned teaching program is effective to improve knowledge of women regarding minor ailments. A finding of the study shows that after conducting planned teaching programmed there was increase in the knowledge regarding minor ailments and its management during antenatal period among primi gravida mothers. Statistically it was found that there is highly significant difference in pre-test and post-test scores. So hypothesis H1 was accepted.